Sivelestat in Patients at a High Risk of Postoperative Acute Lung Injury After Scheduled Cardiac Surgery: A Prospective Cohort Study - Tang YX; Fan ZW; Li J; Pan HD; Su WX; Matniyaz Y; Zhang HT; Luo YX; Lv ZK; Wang WZ; Gao YX; Pan T; et al. (Journal of Inflammation Research, 2024)
Yu-Xian Tang,1,* Zhi-Wei Fan,1,* Jing Li,2,* Hao-Dong Pan,3 Wen-Xin Su,1 Yusanjan Matniyaz,2 Hai-Tao Zhang,4 Yuan-Xi Luo,4 Zhi-Kang Lv,2 Wen-Zhe Wang,2 Ya-Xuan Gao,2 Tuo Pan,2,4 Wan-Zi Xu,1,2 Dong-Jin Wang1– 4 1Department of Cardiac Surgery, Nanjing Drum Tower Hospital, Nanjing Drum Tower Hospital Clinical College, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 2Department of Cardiac Surgery, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, People’s Republic of China; 3Department of Clinical Medicine, Norman Bethune Health Science Center of Jilin University, Changchun, People’s Republic of China; 4Department of Cardiac Surgery, Nanjing Drum Tower Hospital, Peking Union Medical College & Chinese Academy of Medical Sciences, Graduate School of Peking Union Medical College, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dong-Jin Wang; Wan-Zi Xu, Department of Cardiac surgery, Nanjing Drum Tower Hospital, No. 321 Zhongshan Road, Nanjing, Jiangsu, 210008, People’s Republic of China, Email dongjin_wang@126.com; 582321957@qq.comBackground: Sivelestat, a neutrophil elastase inhibitor, is specifically developed to mitigate the occurrence of acute lung injury (ALI) in individuals who are undergoing cardiovascular surgery. However, its impact on patients who are at a heightened risk of developing ALI after scheduled cardiac surgery has yet to be determined. In order to address this knowledge gap, we undertook a study to assess the efficacy of sivelestat in protecting the lungs of these patients.Methods: We conducted a prospective cohort study involving 718 patients who were at high risk of developing postoperative acute lung injury (ALI) and underwent scheduled cardiac surgery between April 25th, 2022, and September 7th, 2023. Among them, 52 patients received sivelestat (administered at a dosage of 0.2mg/kg/h for 3 days), while 666 patients served as controls, not receiving sivelestat. The control conditions were the same for all patients, including ventilation strategy, extubating time, and fluid management. Subsequently, a propensity-score matched cohort was established, consisting of 40 patients in both the sivelestat and control groups. The primary outcome measure encompassed a composite of adverse outcomes, including 30-day mortality, ALI, acute respiratory distress syndrome (ARDS), and others. Secondary outcomes assessed included pneumonia, ventricular arrhythmias, mechanical ventilation (MV) time, and more.Results: After conducting propensity matching in our study, we observed that there were no significant differences in 30-day mortality between the sivelestat and control groups (0% vs 2.5%, P=0.32). However, the use of sivelestat exhibited a significant reduction in the incidence of acute lung injury/acute respiratory distress syndrome (ALI/ARDS) compared to the control group (0% vs 55%, P< 0.01), pneumonia (0 vs 37.5%, P< 0.01), MV time (median:8 hours, IQR:4– 14.8 hours vs median: 15.2 hours, IQR:14– 16.3 hours, P< 0.01). Compared to the control group, the sivelestat could significantly decrease white cell count (P< 0.01), neutrophile percentage (P< 0.01) and C-reactive protein (P< 0.01) in the period of postoperative 5 days.Conclusion: The prophylactic administration of sivelestat has shown promising results in reducing the occurrence of acute lung injury/acute respiratory distress syndrome (ALI/ARDS) in patients with a heightened risk of developing these conditions after elective cardiac surgery. Our study findings indicate that sivelestat may provide protective effects by suppressing inflammation triggered by neutrophil activation, thereby safeguarding pulmonary function.Registration: ChiCTR2200059102, https://www.chictr.org.cn/showproj.html?proj=166643.Keywords: sivelestat, cardiac surgery, acute lung injury, inflammation